Policing the People's University: The Precarity of Sanctuary in the California State University System - Ananth, Akhila L. (Social justice, 2019)
The article discusses the events that occurred across the California State University (CSU) system in 2017, particularly the deployment by administrators of city police officers as a response to the demand for protection by African American and nonwhite students. Also cited are the move by CSU administrators to use city police to prevent student protests in the mid-1960s and the decision to arm police officers deployed in the CSU system in the mid-1970s.